Effects of stereochemistry, saturation, and hydrocarbon chain length on the ability of synthetic constrained azacyclic sphingolipids to trigger nutrient transporter down-regulation, vacuolation, and cell death. Issue 18 (15th September 2016) - Perryman, Michael S.; Tessier, Jérémie; Wiher, Timothy; O'Donoghue, Heather; McCracken, Alison N.; Kim, Seong M.; Nguyen, Dean G.; Simitian, Grigor S.; Viana, Matheus; Rafelski, Susanne; Edinger, Aimee L.; Hanessian, Stephen
Graphical abstract: Abstract: Constrained analogs containing a 2-hydroxymethylpyrrolidine core of the natural sphingolipids sphingosine, sphinganine, N, N -dimethylsphingosine and N -acetyl variants of sphingosine and sphinganine ( C 2 -ceramide and dihydro- C 2 -ceramide) were synthesized and evaluated for their ability to down-regulate nutrient transporter proteins and trigger cytoplasmic vacuolation in mammalian cells. In cancer cells, the disruptions in intracellular trafficking produced by these sphingolipids lead to cancer cell death by starvation. Structure activity studies were conducted by varying the length of the hydrocarbon chain, the degree of unsaturation and the presence or absence of an aryl moiety on the appended chains, and stereochemistry at two stereogenic centers. In general, cytotoxicity was positively correlated with nutrient transporter down-regulation and vacuolation. This study was intended to identify structural and functional features in lead compounds that best contribute to potency, and to develop chemical biology tools that could be used to isolate the different protein targets responsible for nutrient transporter loss and cytoplasmic vacuolation. A molecule that produces maximal vacuolation and transporter loss is expected to have the maximal anti-cancer activity and would be a lead compound.